Utilization of neonatal medication error prevention strategies: a clinical practice survey of Australian and New Zealand neonatal units. (November 2018) - Matti, Nadine; Nguyen, Minh-Nha R.; Mosel, Cassandra; Grzeskowiak, Luke E.
Background: Medication errors are common in neonatal care and can lead to significant harm. We sought to explore utilization of various medication error prevention strategies across Australian and New Zealand neonatal units (NNUs) through a clinical practice survey. Methods: An electronic survey was distributed in October 2016 to relevant staff at each of the 29 level III NNUs identified as members of the Australian and New Zealand Neonatal Network (ANZNN). The survey contained questions relating to a range of medication error prevention strategies identified from a previous systematic review on the topic. The evaluated interventions targeted different aspects of the medication-use process including prescribing, evaluation/checking of orders by clinical pharmacists, transmission, preparation and dispensing of orders, storage of medications, and medication administration. Results: From the 20 respondents, the evidence-based strategies most commonly utilized were use of smart pumps ( n  = 18; 90%), and ward-based clinical pharmacists ( n  = 17; 85%). Interventions least commonly utilized included barcode scanning with medication administration ( n  = 0; 0%), electronic prescribing and clinical decision support ( n  = 1; 5%), and dedicated medication administration nurse ( n  = 2; 10%). The total number of evidence-based medication error prevention strategies utilized in each NNU ranged from 2 to 10 (median = 7), 10 of 16 strategies were utilized by less than 50% of NNUs. Conclusion: While evidence supports utilization of a number of medication error prevention strategies, these appear inconsistently utilized across current practice settings.